IDENTIFICATION OF CHARACTERISTICS AND TYPOLOGY OF COASTAL AREAS AND SMALL ISLANDS OF KOLAKA REGENCY, SOUTHEAST SULAWESI PROVINCE - Gaby Nanda Kharisma; Sudarwin Kamur; Ahmad Iskandar (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2021)
Both the characteristic and the typology distinct the coastal areas dan small island landforms of Kolaka Regency. This paper aims to identify the characteristics and typology of coastal areas and small islands in Kolaka Regency, Southeast Sulawesi Province. The research originates with a literature study and conducts a remote sensing analysis to obtain a tentative map. Furthermore, the terrestrial land survey was carried out using a purposive sampling technique to collect abiotic and biotic data. Semi-structured interviews were conducted to collect the components of cultural data. This study used quantitative and qualitative descriptive. A spatial analysis was also employed to obtain spatial variations that occurred in the study location. Seven measurement stations spread over three districts: Pomalaa, Samaturu, and Wundulako. Pomalaa District consists of two stations: Sweedy Beach and Pelangi Island of coastal genesis in the Marine Deposition Coast. Samaturu District has two stations, Indah Kapu Beach of coastal genesis in the form of Marine Deposition Coast and Konaweha coastal village in Subaerial Deposition Coast. Wundulako District is divided into three stations: Padamarang Island of coastal genesis in the form of Coast Built by Organisms, Lambasina Besar Island with Marine Deposition Coast genesis, and Towua I identified as Coast Built by Organisms. Data on the characteristics and typology of coastal areas and small islands is a preliminary study regarding analyzing Coastal Vulnerability Index (CVI).